Suspected drug-induced hypersensitivity reaction (DRESS Syndrome) following sitagliptin addition in a diabetic patient on glimepiride and metformin: A case report. - Panda, Suvendu Kumar; Dash, Snehasini; Panigrahy, Srikanta; Panda, Manisha; Mahanta, Jasmine; Pradhan, Mousumi (Student's Journal of Health Research Africa, 2025)
Background Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) syndrome is a rare, potentially life-threatening drug-induced hypersensitivity reaction characterized by skin eruptions, eosinophilia, and multi-organ involvement. While rare with antidiabetic drugs, sitagliptin has been implicated in a few reported cases. Objective : To report and analyze a suspected case of Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) syndrome associated with sitagliptin initiation in a type 2 diabetic patient previously controlled on glimepiride and metformin, and to emphasize the importance of early recognition, appropriate management, and pharmacovigilance in rare but serious drug-induced hypersensitivity reactions. Case Presentation We present a case of suspected DRESS syndrome in a 52-year-old male with type 2 diabetes mellitus, who developed facial and limb swelling, skin hyperpigmentation, and systemic laboratory abnormalities five days after sitagliptin initiation. Management and Outcome Sitagliptin was discontinued, and supportive care was initiated. Laboratory abnormalities included leukocytosis, eosinophilia (10%, AEC 1,480 /µL), elevated liver enzymes, and mild renal dysfunction. Symptoms resolved within two weeks following drug withdrawal. Conclusion This case highlights the need for vigilance in recognizing drug-induced hypersensitivity reactions in diabetic patients, even with relatively safe agents like sitagliptin. Recommendation Sitagliptin should be used cautiously after assessing hypersensitivity risk. Monitor for early DRESS signs (rash, facial swelling, eosinophilia) within 2–4 weeks. Educate patients, perform baseline and follow-up labs. Stop the drug at first suspicion; avoid rechallenge and other DPP-4 inhibitors. Report to pharmacovigilance. Skin biopsy and viral tests may aid diagnosis. Further research is needed.